(untitled) (Palíndromo, 2020)
The article is a convergence of ideas derived from the doctoral thesis The Erring Artist and the Discourse as Cartography in a Spanish-Brazilian context (UCM / CAPES), defended in 2017. It raises questions on the artist in the cartographic world and his sinuous and decentralized discourse, trying to analyze the latter as a movement toward the uncertain, a jump into the abyss. In this way, the erring artist, as we defend, is a typology that helps to practice, on the basis of (in)certainties, new ways of thinking and defending art in our day. This contemporary creator wanders and strengthens himself on the maps that his errant discourse (which goes through error) builds in the world. The text goes through concepts such as indecision, singular rhythm, cartography, as well as translation and self-alteration reports.